The young Guarani of Espírito Santo State: Dialogues and cultural workshops - Corrêa de Macedo, Maria Daniela; de Lima Neves, Amabile Teresa; da Silva Ramos Oliveira, Carolini; Manzoli Vedove, Letícia; da Silva, Sérgio Leandro; Sunderhus Pereira, Agnes; Vieira Mota, Vinícius (Guará Journal, 2015)
The following research reports the experience of extension project program Occupational Therapy and the young Indians Guarani of Espírito Santo State: dialogues and cultural workshops between the years of 2011 and 2014, which are related on the Guarani Community and Occupational Therapy students. This project is supported to the necessity of the young Indians Guarani of Aracruz/ES, promoted an analysis for discussion with ethnic profile and incentive to the emancipation using activities that they considered significant to their future prospects, workshops and network groups of activities using resources such as theater, music, dance, multimedia, photography, video and other, as the community work. Thus, the project was justified by the social and cultural imprints that comprehend their actions with the Guarani youth. These actions focused on cultural appreciation, identity assertion, citizenship and social emancipation.